SPECIFIC PRINCIPLES OF USING DICTIONARIES IN LEARNING ECONOMIC TERMS - Yuldasheva Dilnoza Bekmurodovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
In this article, we scientifically studied how to use dictionaries to study economic terms, how to approach the study of specific expressions and important doctrines. In this article, we focused on information designed to improve user experience, improve accuracy, and provide information in the economic field.